The Role of Relawan Jabar Juara in Succeeding Ridwan Kamil-UU Ruzhanul Ulum in 2018 West Java Governor Election - Aria Mahendra Chandra (Epistemik Press, 2021)
Relawan Jabar Juara is a volunteer organization that supporting Ridwan Kamil - Uu Ruzhanul Ulum pair at 2018 West Java Governor Election. This research will explain what is Relawan Jabar Juara's role in supporting Ridwan Kamil - Uu Ruzhanul Ulum pair in campaign period using political campaign concept. In this research, researcher use qualitative approach method and descriptive analysis method for describing Relawan Jabar Juara's role using political campaign concept. Researcher use interview, observation and literature study for collecting data. The result of this research is volunteer's support is very important in Ridwan Kamil - Uu Ruzhanul Ulum win in 2018 regional election, it is all because Relawan Jabar Juara received campaign rule guidebook and insight book about candidate's distinctive feature from the results of analysis by candidate's official supporter team. Second, Relawan Jabar Juara given voted target to be achieved from early survey to make their candidate win. Third, Relawan Jabar Juara appointed to get vote from younger voter. Fourth, Relawan Jabar Juara create campaign message creatively to be delivered to the target. Fifth, campaign message delivered by online and offline. Last, Relawan Jabar Juara actively doing campaign. Relawan Jabar Juara own 62 node spread in West Java.